2021
DOI: 10.3390/ma14030613
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Imaging on Synthesised Nanoparticles

Abstract: Our recently developed non-destructive imaging technique was applied for the characterisation of nanoparticles synthesised by X-ray radiolysis and the sol-gel method. The interfacial conditions between the nanoparticles and the substrates were observed by subtracting images taken by scanning electron microscopy at controlled electron acceleration voltages to allow backscattered electrons to be generated predominantly below and above the interfaces. The interfacial adhesion was found to be dependent on the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This agrees with literature [56] showed that the higher the σ , the more the negative potential energy. Moreover, the difference in the potential energies explains the higher viscosity at low shear rate (around < 0.1 s −1 ) at pH 10 than pH 6 (Figure D‐1(A)) but it cannot be explained by the classical DLVO theory that indicates the higher repulsion with the higher zeta potential of silica particles at higher pH [11]. By comparing Figure 5A–C, they indicate that there is no significant difference on potential energies using different surface charge densities reported in literature that used the same particle type and conditions as our experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with literature [56] showed that the higher the σ , the more the negative potential energy. Moreover, the difference in the potential energies explains the higher viscosity at low shear rate (around < 0.1 s −1 ) at pH 10 than pH 6 (Figure D‐1(A)) but it cannot be explained by the classical DLVO theory that indicates the higher repulsion with the higher zeta potential of silica particles at higher pH [11]. By comparing Figure 5A–C, they indicate that there is no significant difference on potential energies using different surface charge densities reported in literature that used the same particle type and conditions as our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Derjaguin-Landau-Verwey-Overbeek (DLVO) theory is one of the best known theories for describing particle-particle interactions and thus particle dispersion/coagulation with the summation of the van der Waals potential and electrostatic potential. This is a straightforward theory that can explain particle dispersion/coagulation in many different colloidal systems [10][11][12]. On the other hand, there are several cases that the DLVO theory cannot explain, including the cases in high solid concentrations or confined environment.…”
Section: Introductionmentioning
confidence: 99%
“…Elphick et al [ 8 ] applied their scanning electron microscopy (SEM)-based non-destructive imaging technique for the characterization of nanoparticles synthesized using X-ray radiolysis and the sol-gel method. They observed the interfacial conditions between the nanoparticles and the substrates by subtracting images taken by SEM at controlled electron acceleration voltages to allow backscattered electrons to be generated predominantly below and above the interfaces.…”
Section: The Special Issuementioning
confidence: 99%